Analisis Strategi CSR Bank Indonesia dalam Membangun Hubungan Komunitas - Sutarto, Joan; Natalia, El Chris (Jurnal InterAct, 2023)
Corporate Social Responsibility (CSR) is an effort to improve society or communities’ welfare in corporate business operations area. One of the problems in Indonesia is in education, this caused Bank Indonesia to contribute in overcoming the problems through scholarship program and Bank Indonesia scholarships recipients community establishment called New Generation of Indonesia (GenBI). This study aimed to comprehend Bank Indonesia CSR strategy in building community relations. CSR strategy was analyzed by CSR Hierarchy and Triple Bottom Line, while community relations was analyzed by Community Relations Elements and the development and success factors of community relations. This study used a qualitative-descriptive approach with interviews, observation, and document studies as data collection techniques. The results showed Bank Indonesia's CSR strategy was divided into two inseparable programs, and there were efforts to build community relationships. However, communication still needs to be improved, such as through offline meetings to build and strengthen community relations.